Pengembangan Modul Sistem Sirkulasi Berdasarkan Penelitian Hematologi Tikus DMT2 - Badriyatur Rahma Fidiya; Abdul Gofur; Sri Rahayu Lestari (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study aims to develop a circulation system module based on hematological studies of T2DM rats. The module is developed based on the adaptation of the ADDIE developmental model. A module that has been developed then went through validation which is material aspect and teaching materials aspect. Practical tests were carried out by an expert in education practitioners and 10 students who had taken Animal Physiology and Humanities courses at the State University of Malang. The average results obtained from the validation of material experts is 95.8% and teaching material experts 91.4%. While the results of field practitioner expert trials amounted to 97, 9% and based on student responses an average of 90.3% are obtained. Based on these results the module can be said to be very valid and very practical to use in the teaching and learning process. Abstrak: Penelitian ini bertujuan untuk mengembangkan modul sistem sirkulasi berdasarkan penelitian hematologi tikus DMT2. Modul dikembangkan berdasarkan adaptasi model pengembangan ADDIE. Modul yang telah dikembangkan kemudian melalui tahap validasi materi dan bahan ajar. Uji kepraktisan dilakukan oleh ahli praktisi pendidikan dan 10 mahasiswa yang telah menempuh matakuliah Fisiologi Hewan dan Manusia Universitas Negeri Malang. Rata-rata yang diperoleh dari hasil validasi ahli materi 95,8%, ahli bahan ajar 91,4%, uji coba ahli praktisi lapangan 97,9% dan respon mahasiswa rata-rata 90, 3%. Berdasarkan hasil tersebut, modul dapat dikatakan sangat valid dan praktis untuk digunakan dalam proses belajar mengajar.